ANALISIS KUALITAS FRIED CHICKEN HISANA DENGAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Nadia Puspita; Yetti Muthia Hasibuan; Uun Novalia Harahap (Jurnal Industri dan Teknologi Samawa, 2024)
This research aims to determine the causes of the decline in the quality of fried chicken and how to improve the quality of fried chicken at Fried Chicken Hisana using the Quality Function Deployment (QFD) method. The method used in this research is the Quality Function Deployment (QFD) method. The research instrument is a questionnaire distributed to Hisana Fried Chicken consumers. From the results of research based on the QFD method on the HOQ matrix, it is known that the highest value of the temperature parameter in the House of Quality (HOQ) frying process is 124.92 (50.85%). This is because the correlation matrix between the important attributes and the technical parameter attributes influences many attributes such as the level of doneness of the fried chicken, the texture of the creaminess and the aroma of the fried chicken. These results will affect the final quality of the fried chicken. Where the attribute improvement ratio value in this condition, the maturity level has a value of (0.75), which is a high improvement value among other attributes. This shows that these two attributes must be improved and paid attention to by Hisana Fried Chicken. Quality improvement that can be done is by improving the quality of the chicken maturity level attribute by paying attention to the temperature during the frying process.